Constitutional tolerance and chlorophyll fluorescence of Boehmeria nivea L in response to the antimony (Sb) and arsenic (As) co-contamination. Issue 2 (7th February 2017) - Mirza, Nosheen; Mubarak, Hussani; Chai, Li-Yuan; Yang, Zhi-Hui; Mahmood, Qaisar; Yong, Wang; Tang, Chong-Jian; Fahad, Shah; Nasim, Wajid
ABSTRACT: The metal tolerance and metabolic changes in Boehmeria nivea colonized in mining areas are not well known. A hydroponic experiment was conducted to evaluate the impact of antimony (Sb)+arsenic (As) in following combinations (control (no metal), 20+0, 10+10, 40+0, 20+20, and 40+40 mg/L) on phytotoxicity, metal tolerance index (MTI), and chlorophyll fluorescence in B. nivea . This constitutes an initial investigation of metal tolerance and chlorophyll fluorescence in Sb and Sb+As contaminated B. nivea . The high Sb+As 40+40 mg/L produced significant phytotoxicity and MTI in the plant. Progressive higher Sb and Sb+As levels resulted in decreased chlorophyll fluorescence of B. nivea . Exposure to intermediate and high Sb+As levels induced damage in the photosynthesis apparatus of the plant.